Pengaruh Emotional Quotient dan Adversity Quotient Terhadap Prestasi Belajar Matematika Peserta didik Kelas XI SMA - Nur Rachmat; Ilham Minggi; Bernard (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2021)
This study aims to analyze the direct effect of Emotional Quotient (EQ) and Adversity Quotient (AQ) on Mathematics Learning Achievement in class XI SMA. In this analysis, EQ and AQ are independent variables while Mathematics Learning Achievement is the dependent variable. The sampling technique in this study used the cluster proportional random sampling method and the number of samples was 158 students. Data collection techniques, namely by using test and non-test instruments. The instruments used were (1) EQ questionnaire, (2) adversity response profile questionnaire, and (3) mathematics learning achievement test. Methods of data analysis using multiple linear regression analysis techniques. The results showed that: (1) students 'EQ was in the medium category, and students' AQ was in the camper category, while Mathematics Learning Achievement was in the low category, (2) EQ had an influence on Mathematics Learning Achievement, and (3) AQ has no influence on Mathematics Learning Achievement.